EVALUASI PROGRAM GERDU KEMPLING BIDANG EKONOMI DI KECAMATAN PEDURUNGAN KOTA SEMARANG - Tiara Nurfahmi; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
“GERDU KEMPLING” is one of poverty reduction programs which is undertaken by the municipal government of Semarang. The program is led by Regional Development Planning Agency (BAPPEDA) of Semarang which based on five fields namely health, economic, education, infrastructure and environment field. In this study, the writer focused on the field of economic. The research methodology used in the study was qualitative descriptive approach while the data collecting technique used purposive sampling, interview and document study. The informants in the research were Subdivision Head of Development Planning on Governance, Social, Cultural BAPPEDA Semarang, Section Head of Welfare and Social Pedurungan, Section Head of Welfare and Social Plamongansari and Tlogosari Kulon, as well as Pedurungan sub-district society. The research result shows that the implementation of “Gerdu Kempling” program on the economic field in Pedurungan sub-district is not optimal. It is proven by the number of poor people in Pedurungan sub-district which is increased every year. It also does not reach the target of 2% per year. However, there is a village that is successfully empowered, namely Gemah village. While other villages said to be failed. From the result of the research, it can be seen that many poor people in Pedurungan sub-district do not receive any help. A recommendation that can be carried out to increase the implementation of poverty alleviation program in Pedurungan sub-district is the commitment and concern from the whole parties as well as high willingness to create continuity, both on the attention, supervision, and evaluation so that the assistance can be realized and is on target.